SPIRITUAL REVOLUTION IN THE CONTEXT OF THE CONTEMPORARY ERA A REVIEW OF YUSUF QORDAWI'S VISION OF ISLAMIC REVIVAL - Fauzi Ahmad Daud; Eva Dewi; Deni Imansyah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
Spiritual revolution is a phenomenon that has long been discussed in various contexts of human life. One of the figures known as a thinker and writer who raised the theme of spiritual revolution is Yusuf Qordawi. In his works, Qordawi discusses the importance of spiritual transformation in the lives of individuals and society. In the history of Islam there is a very valuable treasure of spiritualism, namely Sufism, it developed following the dialectics of the times since Muhammad SAW was sent until now in the classical Islamic era, Sufism is an individual interest. In the Middle Ages, it turned into a tarekat. Spiritualism in the first generation of Islam served to push history forward and at the same time make life more balanced for underdeveloped communities.